Safety and Efficacy of Early SGLT2 Inhibitors Initiation in Diabetic Patients Following Acute Myocardial Infarction, a Retrospective Study - Gassan Moady MD; Igor Yakubovich MD; Shaul Atar MD (SAGE Publishing, 2024)
Introduction Sodium-glucose cotransporter- 2 (SGLT2) inhibitors have become a cornerstone in heart failure (HF), Type 2 diabetes mellitus (T2DM), and cardiovascular disease (CVD) management. In the current retrospective study, we aimed to assess efficacy and safety of SGLT2 inhibitors early following acute myocardial infarction (AMI). Methods Patients with T2DM hospitalized for AMI in 2017-2020 were divided according to SGLT2 inhibitors therapy status on discharge (with vs without therapy). Primary outcome was defined as a composite of hospitalizations for HF, recurrent AMI, and cerebrovascular accident (CVA). Secondary outcomes included hospitalizations for any cause, total cumulative number of hospitalizations, and all-cause mortality. Results A total of 69 patients (mean age 59.2 ± 8.2 years) with AMI discharged with SGLT2 inhibitors were compared to 253 patients (mean age 62.5 ± 9.8) with no SGLT2 inhibitors. During the first year post-AMI, 4 (5.8%) patients in the treatment group and 16 (6.3%) in the control group were hospitalized for CV events (p = 1.0). Patients in the SGLT2 inhibitors group had lower rates of hospitalization for any cause (31.9% vs 47.8%, P = 0.02), with no change in mortality (0% vs 3.6%, P = 0.21). After multivariate regression analysis, only female gender was associated with increased risk for readmission, mainly due to urinary tract infections. No events of diabetic ketoacidosis (DKA) or limb amputation were reported. Conclusions We found that early initiation of SGLT2 inhibitors in T2DM patients following AMI is safe and decreases the risk of hospitalization for any cause.